A Note on an Abstract Nonlinear delay differential Equation with nonlocal condition ia A new three steps iteration - T. More, Rupesh; M. Sonawane, Pankaj (Journal of Neonatal Surgery, 2025)
In this paper, we study the existence, uniqueness and other properties of solutions of an abstract nonlinear delay differential equation with nonlocal condition. The tool employed in the analysis is based on application of new three steps iteration. New three steps iteration method has equally important contribution to study various properties such as dependence on initial data, closeness of solutions and dependence on parameters and functions involved therein.A new three steps iteration process introduced by V. Karakaya,Y. Atalan, K. Dogan, and NH. Bouzara [8]..